Educational policy actors as stakeholders in the development of the collective skill system - Gonon, Philipp [Verfasser]; Maurer, Markus [Verfasser] (My University, 2012)
"The historical development of Switzerland’s collective skill formation system is strongly interrelated with the structure and overall trajectory of the country’s political economic system. From early industrialization until the present, cleavages have existed not only between the federal state and the cantons, between the representatives of employers and the labor force but also between different factions of the key stakeholders in the political economy (i.e., employers’ associations, labor movement, and political parties). As a consequence, educational stakeholders and the federal administration have played a key role in the development of the skill system. In this context, apprenticeship training has continued to be a widely accepted model of skills provision and thus to form the core of the Swiss vocational education and training (VET) system. Nevertheless, this system has been adapted in recent years to ensure that more general and academic skills are being provided." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 3.5.4 Sozialpartner; I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsbildungspolitik; Sozialpartner; Historische Entwicklung; Schweiz